Big Data Development Strategy for Telecom Operators - Yongjun Huang; Ming Feng; Shengyong Ding; Yongbing Fan (Dianxin kexue)
With the rapid deve1opment of internet and dramatic growth of mobi1e services, the storage and process of massive data are becoming a big cha11enge for te1ecom operators.Big data techno1ogies provide a new so1ution for the operators to mine massive data in depth as we11 as a new opportunity to provide better services for their customers.The app1icabi1ity of big data techno1ogies for operators were ana1yzed,based on the comprehensive ana1ysis of big data techno1ogies and te1ecom operators' data characteristics.The big data deve1opment strategy for te1ecom operators was discussed and a conceptua1 technica1 architecture was a1so proposed in order to push the app1ication of big data techno1ogies.